2015
DOI: 10.1002/srin.201500063
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation of Indefinite Chill Roll Material Under Dry and Humid Atmospheres

Abstract: In this paper, the isothermal oxidation of the indefinite chill (IC) roll is investigated by using a thermogravimetric analyzer (TGA) from 550 to 700 °C under dry and humid atmospheres. It is found that the oxidation kinetics follow a linear trend and the oxide scale consists of two layers after the oxidation in dry air but three layers in humid air above 600 °C. In dry air, the graphite is covered by the oxide scale above 650 °C. The water vapor accelerates the oxidation of the matrix and the graphite. The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Because the numbers of cobbles, double folded strip and tail end pinches increase in the later stands of a hot strip mill, mechanical cracks seem to grow deeper in HSS than that in IC rolls [6]. Moreover, during the hot rolling of stainless steels, it is also reported that the sticking defects are obviously improved with the application of IC rolls, since the graphite in the IC materials can retard crack propagation and reduce friction [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the numbers of cobbles, double folded strip and tail end pinches increase in the later stands of a hot strip mill, mechanical cracks seem to grow deeper in HSS than that in IC rolls [6]. Moreover, during the hot rolling of stainless steels, it is also reported that the sticking defects are obviously improved with the application of IC rolls, since the graphite in the IC materials can retard crack propagation and reduce friction [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Image analysis of its BSE image reveals that the total area fraction of these carbides is 12.5%, including 8.5% MC and 4.0% M 7 C 3 and M 6 C. In addition, there are three different phases(Fig. 2b), graphite, cementite (Fe 3 C) and tempered martensite in the IC[7], comprising 4.3% graphite and 20.8% cementite. The HSS has a high hardness of 760 HV whereas the IC has a lower hardness of 633 HV.…”
mentioning
confidence: 99%
“…The mass variations were recorded in this process. The air containing 20% water vapor was obtained by setting the temperature of the water tank at 60 • C [31].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 7 shows SEM images of the IC cross section of the matrix regions and the graphite areas oxidized at 700 • C in both dry and humid air. As the IC rolls oxidized in the dry air (Figure 7a,b), two relatively thin oxide scales can be observed, namely a thin Cr-rich (FeCr) 3 O 4 layer next to the substrate, and an outer layer of hematite (Fe 2 O 3 ) [31]. The oxidation of graphite is known as decarburization and left an amount of cavities, which were filled by the extension of the oxide scales.…”
Section: Cross Section Examinationmentioning
confidence: 99%
“…Wei et al investigated the effect of water vapor content on high‐temperature oxidation behavior of stainless steels by using the water vapor content from 2.8 to 19.5 vol%. Literatures also reported the influence of water vapor on oxidation process of different steels and illustrated that water vapor as corrosive gas in high‐temperature oxidation process changes the oxidation behavior of metals compared to dry air. Therefore, it is essential to understand the effect of water vapor on the high‐temperature oxidation behavior of Cr‐containing steels because water vapor can play the key role in changing the oxidation behavior.…”
Section: Introductionmentioning
confidence: 99%